1994
DOI: 10.14430/arctic1306
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Compounds in the Plasma of Peregrine Falcons and Gyrfalcons Nesting in Greenland

Abstract: ABSTRACT. Levels of organochlorine compounds in the blood plasma of after-second-year female peregrine falcons (Falco peregrinus) were determined from samples collected from southern Greenland in 1985 and western Greenland from 1983 to 1989, and from adult and nestling gyrfalcons (Falco rusticolus) from western Greenland in 1989 and 1990. Samples were taken during nesting. Levels of p,p'-DDE (DDE) in peregrine plasma were 140 µg/kg wet weight geometric mean (GM) for the southern samples, and 220 µg/kg GM for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…We believe that peregrine falcons that breed near Rankin Inlet no longer face a direct threat from the pollutants investigated in this study, and in this regard, there is good reason to be optimistic about the future of peregrine falcons breeding at Rankin Inlet. Similar trends have been noted previously by other authors (Jarman et al, 1994;henny et al, 1996Ambrose et al, 2000;Clark et al, 2009) investigating pollutant levels in peregrine falcons in other jurisdictions, and we suggest that this trend most likely applies to other Canadian populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We believe that peregrine falcons that breed near Rankin Inlet no longer face a direct threat from the pollutants investigated in this study, and in this regard, there is good reason to be optimistic about the future of peregrine falcons breeding at Rankin Inlet. Similar trends have been noted previously by other authors (Jarman et al, 1994;henny et al, 1996Ambrose et al, 2000;Clark et al, 2009) investigating pollutant levels in peregrine falcons in other jurisdictions, and we suggest that this trend most likely applies to other Canadian populations.…”
Section: Discussionsupporting
confidence: 92%
“…Remarkably, there exist relatively few studies of the toxicological status of North American peregrine populations during this recovery era. Court (1993) assessed the toxicology of peregrine falcons (F. p. anatum) breeding in Alberta, Canada, between 1968and 1992, while Court et al (1990 and Johnstone et al (1996) reported on the toxicology of the Rankin Inlet population from 1982 to 1986to 1994, respectively. Jarman et al (1994 reported on organochlorine compounds in the plasma of peregrine falcons nesting in greenland.…”
Section: Introductionmentioning
confidence: 99%
“…Each unmarked bird was banded with a numbered Danish band on the right tarsus and an alphanumeric color band on the left tarsus (i.e., the opposite of the protocol for nestlings). Prey remains were collected for several years to describe food habits (Rosenfield et al, 1995), as were nestling blood samples for environmental contaminants (Springer et al, 1984;Jarman et al, 1994) and parasite analyses (Taft et al, 1998).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Egyptian vultures in Spain showed levels ranging from means of 0.54-4.1 ng/ml in serum (maximum value 20) (Gomara et al 2004). Adult peregrine falcons had mean PCB 153 concentrations of 47 and 120 ng/ml in plasma (maximum value 220) in 42 birds from two areas in Greenland (Jarman et al 1994). Considering these sparse data in raptors, the levels of the PCB 153 congener \0.17 ng/ml (equivalent to approximately 0.4 ng/ml in plasma or serum) in GV in this study appear to be lower than levels of expected detrimental effects.…”
Section: Pcb 153 Congenermentioning
confidence: 60%
“…In the Accipitridae family, mean concentrations ranging from approximately 4-23 ng/ml in plasma were found in sharp-shinned hawks (Accipiter striatus) on migration (Elliott and Shutt 1993). Adult peregrine falcons (Falco peregrinus) in the Falconiformes order had mean oxychlordane concentrations of 18 and 26 ng/ml (maximum value 57) in plasma of 42 birds from Greenland (Jarman et al 1994), compared with 20 ng/ml (maximum value 140 ng/ml) in plasma of 34 female birds in the Canadian tundra (Johnstone et al 1996). Considering these few data in diurnal raptors, the levels of oxychlordane \0.47 ng/ml (equivalent to approximately 1 ng/ml in plasma) in GV in this study appear to be lower than levels of expected detrimental effects.…”
Section: As and CDmentioning
confidence: 99%